Rubber world price transmission to Ivorian producer prices: An analysis in the presence of structural breaks - Mélanie Ahoba; Frédéric Gaspart (Agricultural and Food Economics, 2019)
This article analyzes the link between world prices and producer prices of rubber in Côte d'Ivoire. Using monthly data from 2006 to 2016, we gave special attention to structural breaks in the data and asymmetry in the transmission process. Empirical results validate the presence of two breaks in the data series, both in 2008 and 2011 corresponding to a general surge in commodity prices. A multivariate threshold vector error correction model (TVECM) allows us to test the presence of asymmetry. The results strongly support the linearity hypothesis against k-regime TVECM. From there, a linear VECM reveals that changes in rubber world prices are strongly transmitted to Ivorian producer prices. In case of a world price permanent decrease, this will be devastating for small producer incomes, since financial markets are essentially missing in those rural areas and switching costs for perennial crops are huge. Some recommendations are given to prevent such a crisis.
Keywords: 330; Price transmission; Rubber; Threshold cointegration; Côte d'Ivoire; Structural breaks